Plan de manejo integral del Parque Orillas del Zamora. - Rengel Roman, Jorge Luis (2015)
The main objective is to conduct a comprehensive management plan Shores Zamora Park is located in the city of Loja, for it was raised specific objectives making a diagnosis based on its maintenance to design the management plan by carrying out programs to improve their surveillance and security, public use, maintenance and control, the park serves trails for sport and has a street furniture for rest, playgrounds and sulfur water baths, is provided with green areas providing a landscape of relaxation such as the path kartódromo, nursery, orchid and sulphurous waters, hence the importance of conservation areas and proper maintenance. The results found that the park if you have maintenance green areas, part of the furniture, but otherwise the signage in poor condition and lack of definition of the path trails, also stretches of the banks of the river Zamora shabby. In conclusion, the implementation and improvement of urban furniture is also necessary to give the lighting in certain areas, also provide a cleaned up at the entrances to the park and continue closing the park.